ANALISA PERANCANGAN FILTER PASIF UNTUK MEREDAM HARMONIK PADA INSTALASI BEBAN NONLINEAR - Hari Prasetijo (Universitas Muhammadiyah Purwokerto, 2012)
Non-linear loads increasing on a power system results in harmonic distortion (THD) increasing. Harmonic distortion increasing getting bad influences on power system components. Measurement at one of PLN's customer installations with many non-linear loads shows the amount of voltage THD 9.41% and current THD 15.05%. To reduce the harmonic distortion we can use harmonic filters. The filter designed is a single-tunned passive filter. The design of harmonic filters adapted to the dominant order occured. Filters are not only used to reduce harmonic distortion occurred but also increase power factor. From the simulation results that by installing a single-tunned passive filters on the system, voltage THD has decreased from 9.41% to 6.61% while the current THD decreased from 15.05% to 10.40%. Meanwhile, system power factor increased from 0.971 to 0.992. Keywords: Total Harmonic Distortion, Passive Filter, Nonliear Load